Evaluating Classroom Management Strategies to Prevent Violence in Elementary Schools: A Case Study in Palu City, Indonesia - Yusdin Mahmudin Gagaramusu; Zulnuraini Zulnuraini; Shalehuddin Shalehuddin; Ammar Abdullah Joni Guci; Danti Indriastuti Purnamasari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Violence in elementary schools, particularly verbal and bullying behavior, remains a persistent issue in Palu City, Indonesia. Weak supervision, inadequate classroom management, and the normalization of violence contribute to an unsafe learning environment. This study evaluates the effectiveness of classroom management strategies in preventing student violence. A convergent mixed-methods approach was employed involving 30 participants (teachers and students) from three elementary schools in Palu. Quantitative data were gathered through structured questionnaires, while qualitative data were obtained via interviews and observations. Instrument reliability was verified using Cronbach's alpha (0.60), and thematic analysis was used for qualitative insights. Findings show that 86.7% of students had witnessed or experienced violence, with verbal abuse (46.7–63.6%) and bullying (20.7–27.3%) being the most common. Violence predominantly occurred in the schoolyard (90.9%), indicating weak supervision. Common teacher practices included establishing rules (90.9%) and reprimanding violators (93.5%), though only 45.2% incorporated conflict management strategies. Despite this, 82% of teachers rated their classroom management as effective or very effective. Although teachers are proactive in rule enforcement, gaps remain in conflict resolution and empathetic communication. The study highlights the need to shift from reactive to proactive management by integrating character education, positive reinforcement, and restorative practices. A whole-school approach involving consistent supervision, teacher training, and inclusive policies is essential to foster a safe and supportive school culture.